Research of key factors affecting the profit of mini-hotel in project to improve its performance - Левыкин, Виктор Макарович; Дэвон, Валерия Викторовна (Technology audit and production reserves, 2015)
The article deals with the concept of quality of services and the needs of consumers, as the main factor affecting the profits of mini-hotels. A survey of customers of mini-hotels is organized to identify the factors influencing their choice of hotels and their satisfaction. (Quantitative and questionnaire methods were used to collect the data in this investigation). Number of outputs was collected in a survey of 30,000 guests of mini-hotels of Ukraine. Research of consumer demand in the hospitality market, through statistical studies has established exactly what customers want. The golden rules of customer service in mini-hotels are formulated. Practical recommendations are shown and advices for hoteliers are given. The conclusions of the discussion of the research results can be used by managers of mini-hotels to improve quality control of hotel service in hotels. The results of research will help hoteliers identify the list of services that is really demand and improve the quality of services to meet customers and increase profits.